Economic Well Being of Women Through Self Help Groups: A Study in Dharmapuri District of Tamil Nadu - Lakshmi, R.; Vadivalagan, G. (Prabandhan: Indian Journal of Management, 2011)
Developing countries lay more stress on women development and their active participation in the main stream of development activities. Self help group (SHG) programmes, often in the form of credit or micro credit schemes, and savings have succeeded in changing the lives of poor women by making way for enhanced income and increased self-esteem. In Tamil Nadu, a SHG Project under the name of "Mahalir Thittam" has now grown into a mammoth movement covering all districts in the state, targeting poor families and the marginalized sections of the society. The present study is an attempt to study the role of SHGs in ameliorating the economic position of women in Dharmapuri district of Tami Nadu. Income, savings and expenditure indicate the economic position of a person, hence, a comparison between the income, savings, and expenditure of the respondents in the pre-SHG period and post SHG period is made. The benefits derived by the members after joining the group is highlighted upon. The major findings of the study have been enumerated.